2015
DOI: 10.3233/ch-141857
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous responses of personalised high intensity interval training on type 2 diabetes mellitus and cardiovascular disease risk in young healthy adults

Abstract: Hypertension, decreased glucose tolerance, adverse lipid profiles and low physical activity levels are associated with increased type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD) risk. High intensity interval training (HIIT), a low volume, reduced time, high intensity programme, may be a useful alternative to current government guidelines which specify a minimum of 150 minutes of physical activity per week. We describe a personalised programme of high intensity exercise which provides significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
1
28
0
6
Order By: Relevance
“…Similarly, a NRs prevalence in decreased systolic BP of 12.2% was reported after endurance training (30–50 min/session, 3 days/week, 55–75% Vo 2 max, 20 weeks) in a study assessing a wide sample of subjects (Bouchard et al, 2012). Other HIIT-based studies in adults have reported a NRs prevalence in terms of decreased diastolic BP of 61.5%, and our study is in accordance with this finding, reporting a value of 58.8% (Higgins et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a NRs prevalence in decreased systolic BP of 12.2% was reported after endurance training (30–50 min/session, 3 days/week, 55–75% Vo 2 max, 20 weeks) in a study assessing a wide sample of subjects (Bouchard et al, 2012). Other HIIT-based studies in adults have reported a NRs prevalence in terms of decreased diastolic BP of 61.5%, and our study is in accordance with this finding, reporting a value of 58.8% (Higgins et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…Evidence has shown the benefit in terms of decreased systolic blood pressure after HIIT interventions (Ciolac, 2012); however, in this non-hypertensive cohort, we did not observe significant training-induced changes in systolic or diastolic blood pressure (Table 2). In other studies, there was an ~60% NRs prevalence for decreased systolic or diastolic blood pressure after 6 weeks (Higgins et al, 2015) or 6 months (Moker et al, 2014) of HIIT. Interestingly, a study that explored the magnitude of the changes in blood pressure after an acute exercise session reported that this response can be used as a predictive factor for decreases in blood pressure after long-term exercise training (Hecksteden et al, 2013a).…”
Section: Discussionmentioning
confidence: 84%
“…There is limited evidence about interindividual variability in exercise training with regard to the NRs prevalence in subjects with low glucose control, and there are several methodological differences in studies comparing the NRs prevalences observed in previous studies (Boulé et al, 2005; Gremeaux et al, 2012; Yates et al, 2013; Moker et al, 2014; Winett et al, 2014; Higgins et al, 2015). For example, for glucose control variables, several authors have observed that after 3 months of strength training (2 days/week, 2 strength exercises at maximal effort), the NRs prevalence for improvements in an OGTT in pre-diabetic patients was 44%.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior a un programa de HIIT (6 semanas), Higgins y cols. 35 reportaron una prevalencia de NRs de un artículo de investigacióñ 60% para reducir la PAS y PAD. Bouchard y cols.…”
Section: Discussionunclassified